2024
DOI: 10.1136/bmjopen-2023-078511
|View full text |Cite
|
Sign up to set email alerts
|

Comparing physician associates and foundation year 1 doctors-in-training undertaking emergency medicine consultations in England: a quantitative study of outcomes

Nicole Marjorie Andrea King,
Suzannah Helps

Abstract: ObjectivesTo compare the contribution of physician associates (PAs) to the outcomes of emergency medicine consultations with that of foundation year 1 doctors-in-training (FY1s).DesignA quantitative study using retrospective chart review of adult patients seen by PAs or FY1s from August 2018 to January 2020 using 16 months of anonymised clinical record data.SettingOne emergency department (ED) in England.ParticipantsThe outcomes of 7405 patients seen by 11 PAs and 7 FY1s were recorded, with n=4580 PAs and n=28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…According to our study, some patients mistakenly believed that they were being treated by a doctor. The misconception of PAs as doctors has also been noted in other UK studies [ 38 , 39 , 40 , 41 ]. Despite the PA role being present in the United States for over 60 years, a survey conducted in 2021 showed that the PA role confusion is longstanding with 25% of patients wrongly believing PAs to be doctors [ 43 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…According to our study, some patients mistakenly believed that they were being treated by a doctor. The misconception of PAs as doctors has also been noted in other UK studies [ 38 , 39 , 40 , 41 ]. Despite the PA role being present in the United States for over 60 years, a survey conducted in 2021 showed that the PA role confusion is longstanding with 25% of patients wrongly believing PAs to be doctors [ 43 ].…”
Section: Discussionsupporting
confidence: 56%
“…Other studies have also found PAs' documentation to be thorough [ 21 , 37 , 38 ] and there was a suggestion that the ED metrics may be affected because of the level of PA documentation [ 39 ]. Our study could have been enhanced if combined with impact metrics [ 40 ] and or included observations of case notes [ 39 ] to better experience the level of PA patient documentation and its effects on the department throughput.…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of MAPs is particularly important during times of doctor shortages and rota gaps 14,15,16 . In UK emergency departments, MAPs have been shown to work at an equivalent level to foundation year one and two doctors, with similar outcomes, and provide safety and continuity to the team 17,18,19 . Generally, patients report good levels of satisfaction with MAPs.…”
Section: Sushruta Journal Of Health Policymentioning
confidence: 99%